PERUBAHAN PERILAKU KEAGAMAAN SATU KELUARGA PASCA MENUNAIKAN IBADAH UMRAH DI KECAMATAN MARANG KBUPATEN PANGKEP (STUDI KASUS) (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
The main problem of this research is how to change the religious behavior of a family after performing Umrah in Marang District, Pangkep Regency. Then, the main problem is described into sub-problems, namely: 1) What is the change in a family's religious behavior after performing the Umrah in Marang District, Pangkep Regency? and 2) What are the views of the local community about the changes in the religious behavior of a family after performing the Umrah Service in Marang District, Pangkep Regency?The type of this research is a case study with qualitative research methods, the research approach is a scientific approach to Hajj and Umrah Management and a Psychology approach. The research data sources are primary and secondary data sources, primary data sources consist of one family who has performed Umrah, in this case, the father, mother, children, and the local community that consisted of five informants. Secondary data sources are books, journals, and articles. Data collection methods used in this study were observation, interview, and documentation. Data processing techniques and data analysis were carried out through four stages, namely: data collection, data reduction, data presentation, and conclusion.The results of this research indicate that there is a change in a family's religious behavior after performing the Umrah, which can be in terms of worship discipline, in this case, is the discipline in carrying out the five daily prayers in congregation, maintaining attitudes, social care and always establishing a relationship with other people, in this case, the relationship with other people and their relationship with Allah. In the public's view of the changes in a family, religious behavior after performing the Umrah is true that it has changed for the better which can be seen from the way of communicating with the community, besides that, discipline in worship extends a positive influence on the community, therefore, people feel interested or willing to perform Umrah.